1994
DOI: 10.2466/pr0.1994.75.2.911
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Smoking Status by Symptoms of Depression for U.S. Adolescents

Abstract: Abstract:Summary.-This study examined the predictive relationships between adolescents' smoking and symptoms of depression. A national sample of 6,900 adolescents, ages 14 to 18 years, were selected for analysis. Variables of interest included measures for smoking status and symptoms of depression. Odds ratio and adjusted odds ratio from logistic regression analyses indicated that more of the 885 smokers than of the 6,015 nonsmokers reported feelings of unhappiness, sadness, or depression, hopelessness about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
13
0
4
Order By: Relevance
“…3 Depression is a factor that may be important. Cross-sectional studies of adolescents showed that depression was related to a variety of unhealthy behaviors, such as cigarette smoking, 4 alcohol consumption, 5 and substance use. 6,7 In longitudinal studies, depressive symptoms in teenagers aged 15 to 16 years were positively related to the teenagers' smoking status 9 years later, 8 a previous diagnosis of major depressive disorder was 3 to 4 times more common in students with a history of alcohol abuse or substance use than in control subjects, 9 and depressed mood predicted first-time use of marijuana and other illicit drugs in secondary-school students.…”
mentioning
confidence: 99%
“…3 Depression is a factor that may be important. Cross-sectional studies of adolescents showed that depression was related to a variety of unhealthy behaviors, such as cigarette smoking, 4 alcohol consumption, 5 and substance use. 6,7 In longitudinal studies, depressive symptoms in teenagers aged 15 to 16 years were positively related to the teenagers' smoking status 9 years later, 8 a previous diagnosis of major depressive disorder was 3 to 4 times more common in students with a history of alcohol abuse or substance use than in control subjects, 9 and depressed mood predicted first-time use of marijuana and other illicit drugs in secondary-school students.…”
mentioning
confidence: 99%
“…These studies showed that depression was associated with (a) current smoking at the time of the study 3 , (b) the frequency of cigarette use 4 , (c) the progression to higher stages of smoking (LloydRichardson, Papandonatos, Kazura, Stanton, & Niaura, 2002), and (d) regular smoking (Acierno et al, 2000;Boys et al, 2003;Patton et al, 1996;Simantov, Schoen, & Klein, 2000;Wang et al, 1994).…”
Section: Significant Associations In Cross-sectional Studiesmentioning
confidence: 99%
“…Among the 18 studies that did not use validated de-pression instruments, 10 were cross-sectional studies, and all of these studies found the statistically significant relationship between smoking and depression (Boys et al, 2003;Brooks et al, 2002;Coogan et al, 1998;Covey & Tam, 1990;Landrine et al, 1994;LloydRichardson et al, 2002;Martini et al, 2002;Otsuki, 2003;Pesa, Cowdery, Wang, & Fu, 1993;Wang et al, 1994). Five of eight longitudinal studies found the statistically significant relationships between smoking and depression: Three studies found depression as an antecedent to smoking, and two studies found the bidirectional relationship between smoking and depression (Dierker et al, 2004;Fleming et al, 2002;Gilpin et al, 2004;Goodman & Captman, 2000;Wang et al, 1996).…”
Section: Measurement Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies show that symptoms of depression predict initiation, [16][17][18] experimentation, 18,19 and regular cigarette smoking. 20,21 Given that women are twice as likely to experience major depression and that the onset of major depression coincides with the first years of college, 22 the ability of nicotine to dispel depression effectively 23,24 may act as a powerful smoking reinforcer for young first-year college women.…”
mentioning
confidence: 99%